Hyperbaric oxygen treatment of superficial soft tissue lesions in children with oncologic disease - Eleonora Cesca; Giacomo Garetto; Emanuela Frascella; Simone Cesaro; Patrizia Dall'Igna; Giovanni Cecchetto (MDPI AG, 2011)
This study aimed to assess the feasibility and results of hyperbaric oxygen therapy (HOT) as supportive treatment of lesions of superficial soft tissues in children with oncological diseases. This was a retrospective analysis and review of all records of children observed at the Pediatric Hematology-Oncology Department of the University of Padova and treated adjuvantly with HOT. Between 1996 and 2010, 12 patients (5 males and 7 females, median age 7 years, range 0.5-16) underwent HOT. The effectiveness of HOT varied according to the lesion treated. Ten out of 12 patients were cured. Efficacy was most questionable in 2 patients with skin graft and flaps at risk. Compliance to therapy was close to 100%. In just one case, HOT was interrupted for the appearance of local skin metastases close to the site of primary tumor. HOT showed itself to be safe and effective in most patients even those immunocompromised or critically ill.